2017
DOI: 10.17221/187/2015-pps
|View full text |Cite
|
Sign up to set email alerts
|

Negative correlations between the susceptibilities of Czech and Slovak pollen beetle populations to lambda-cyhalothrin and chlorpyrifos-ethyl in 2014 and 2015

Abstract: Seidenglanz M., Poslušná J., Kolařík P., Rotrekl J., Hrudová E., Tóth P., Havel J., Plachká E., Táncik J., Hudec K. (2017)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…3). Similar to our own findings, a decrease in susceptibility levels to thiacloprid has also been reported in Poland (Seidenglanz et al 2017). Over a relatively long period now, the Estonian pollen beetle population has been exposed to insecticides, but a systematic resistance testing of the pollen beetle population had not been carried out prior to 2015.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…3). Similar to our own findings, a decrease in susceptibility levels to thiacloprid has also been reported in Poland (Seidenglanz et al 2017). Over a relatively long period now, the Estonian pollen beetle population has been exposed to insecticides, but a systematic resistance testing of the pollen beetle population had not been carried out prior to 2015.…”
Section: Discussionsupporting
confidence: 88%
“…Severe damage is caused by beetles feeding during early budding stages, leaving podless stalks after flowering and reducing yields (Williams and Free 1978, Ekbom and Borg 1996, Williams 2010. The long-term intensive use of insecticides has led to the development of resistance in many countries, such as Germany (Heimbach et al 2006), Denmark (Hansen 2003, Hansen 2008, Kaiser et al 2018, Czech Republic (Seidenglanz et al 2017, Stará and Kocourek 2018, Spitzer et al 2020, Poland (Wegorek and Zamoyska 2008, Węgorek et al 2009, Philippou et al 2011, Finland (Tiilikainen and Hokkanen 2008), and Lithuania (Makūnas et al 2011(Makūnas et al , Šmatas et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, B. aeneus has developed high levels of resistance to pyrethroid insecticides in several areas across Europe (Slater et al 2011;Heimbach and Müller 2013;Zamojska 2017;Stará and Kocourek 2018;Kaiser et al 2018). While neonicotinoid insecticides are also being applied in B. aeneus management (Seidenglanz et al 2017;Kaiser et al 2018), exposure to neonicotinoids has shown negative effects on a wide range of nontarget organisms (Gibbons et al 2015;Pisa et al 2017;Willow et al 2019;Berheim et al 2019;Calvo-Agudo et al 2019;Wu et al 2019). For example, in oilseed rape agroecosystems, nontarget organisms negatively affected by thiacloprid applications could include economically important parasitoids of B. aeneus, given that laboratory studies have demonstrated the detrimental effect of thiacloprid on other parasitoid wasps (Sugiyama et al 2011;Jans 2012;Willow et al 2019).…”
Section: Introductionmentioning
confidence: 99%